Negotiating Identities: A Study of Monica Ali’s in the Kitchen and Mohsin Hamid’s The Reluctant Fundamentalist - Mausumi Pattanayak; Dr. Mukesh Tiwari (Educational Administration: Theory and Practice, 2024)
Negotiating identities refers to the process by which individuals or groups actively construct, redefine, and sometimes challenge their sense of self or collective identity in response to both external and internal influences. This process typically takes place in contexts where multiple, and often conflicting, cultural, social, political, or personal factors are at play. Negotiating identity entails an ongoing interaction between how one perceives oneself and how others perceive or categorise them. This paper explores the theme of identity negotiation in Monica Ali’s In the Kitchen and Mohsin Hamid’s The Reluctant Fundamentalist, two contemporary novels that address the complexities of personal, cultural, and political identity within the contexts of globalisation and migration. Ali’s In the Kitchen follows Gabriel Lightfoot, a British chef who contends with the challenges of working in a multicultural London environment, while Hamid’s The Reluctant Fundamentalist depicts Changez, a Pakistani man whose sense of self is dramatically reshaped by the cultural and political upheavals following 9/11. Both novels emphasise the fluid nature of identity, illustrating how forces such as immigration, racial tensions, and geopolitical conflicts impact personal self-perception. Through their protagonists’ journeys, the novels highlight the ongoing negotiation of identity in a world where the boundaries between East and West, tradition and modernity, and the personal and political are constantly shifting. This paper analyses how Ali and Hamid present the challenges of self-definition in a globalised world, revealing the psychological, emotional, and social aspects of identity formation and transformation.